The effect of purple rice (Oryza sativa L. indica) extract on the inflammatory response in a colon cancer cell line and dextran sulfate-induced tumor promotion in the rat colon - Warunyoo Phannasorn (2018)
© 2017, The Korean Society of Toxicogenomics and Toxicoproteomics and Springer Science+Business Media B.V., part of Springer Nature. This study investigated the effects of purple rice extract (PRE) on inflammation-related colon carcinogenesis. Administration of PRE 1 g/kg bodyweight reduced both the number (39.05%) and size of aberrant crypt foci (ACF) (14.28%) in the colons of rats that received dimethylhydrazine (DMH) initiation with promotion by dextran sulfate sodium (DSS) (P < 0.05) with the reduction of TNF-α expression in colonic epithelial cells. On the other hand, PRE could suppress the expression of both TNF-α and IL-6 in RAW 264.7 cells activated by lipopolysaccharide (LPS) at both the mRNA and protein levels. Moreover it could reduce the expression of TNF-α and IL-1β mRNA in inflamed HT-29. These findings suggested that PRE is able to modulate the inflammatory process in both activated macrophages and colon cancer cells. Therefore, PRE suppressed macrophage activation and colon cancer cell line response to inflammation and modulated of inflammation induced ACF progression in the rat colon.